PERSEPSI MASYARAKAT TERHADAP PENGELOLAAN AGROFORESTRI DI TAHURA WAN ABDUL RACHMAN, BANDARLAMPUNG - Yeni Susanti; Christine Wulandari; Slamet Budi Yuwono; Hari Kaskoyo; Rahmat Safei; Rahmat Safei (Jurnal Hutan Tropis, 2021)
Wan Abdul Rachman Forest Park (Tahura WAR) is one of a forest area located on Register 19 Lampung. Based on literature and research results in Tahura WAR, there had not been many reports of people perceptions for the agroforestry management, so it is necessary to conduct research to determine people involvement in forest management with agroforestry cropping patterns. The research was conducted from February to March 2020 in Sumber Agung Village, Bandar Lampung City. Sampling using purposive with a total 36 respondents and data collection using observation techniques, interviews with questionnaires, literature study and documentation. Data were analyzed using a qualitative descriptive method with a 1-3-5 scaling (Likert Scale Modification). The variables used are the social characteristics and people perceptions for the agroforestry management as seen from the indicators including community knowledge about forest management, forest protection, wildlife livelihoods, collection of forest products and agroforestry economy. Based on the results of the study, the social characteristics consist of low education level (SD-SMP) was 86,11%, the age dominated by the medium category (30-45 years was 61,11%, and the number of dependents in the medium category (3-4 people) was 66,67%. People perception for the agroforestry management was affected by ecological and economic aspects. Based on the ecological aspect, the overall perception of the community was classified as moderate. In detail, the perception analysis of ecological aspects were as follows: 78.81% in understanding the utilization of the forest area, 100% in understanding land processing, 60% understanding land clearing, 85.94% understanding reforestation measures, 77.21% not understanding insect pest control and 91.07% understanding disease management. Meanwhile, the people perception of grazing livestock, clearing forest land, actions when encountering animals and controlling wildlife was 100% understanding. Based on the economic aspect, People perception for the agroforestry management was classified as low because 100% not understanding the benefits of non-timber forest products (NTFPs) in the agroforestry system, 70% understanding the types of plants that have economic value, and 85% not understanding the value the importance of agroforestry in Tahura WAR on community income.